التبني بين الشريعة الإسلامية والقانون الإندونيسي - Baqir, Zaenal Abidin Mochamad; Arif, Arif Ali; Zaim, Muntaha Artalim (Al-Hikmah Research a& Publication Centre, 2021)
This jounal discusses The meaning of Adoption in Indonesian Law.does the adoption system implemented in Indonesian Include adoption that are prohibited in Islam? or it is just a system to help the development of children when there are no classical instrument such as parent and family or have other meanings than that? In this journal I use Analysis & survey methods.so I collected point related to adoption in the holly quran, sunnah & book Of Islamic law and I intend to arrive at the nature of adoption and the reason for its prohibition in sharia along whith looking at the nature of adoption in Indonetian law. So if these reason are missing then adoption is allowed and this is the conclusion a reached when I saw the points in the Indonesian law relating to adoption, it turn out that it is only a system to help a child grow and develop whithout violating the child’s human rights in islam, likewise among the hadiths of this journal are the sentences that the “ adoption” in Indonesian law is different from the adoption that is haram in the shari’a in terms of its meaning, so between the two only the same vocabulary but different law and meanin